Characteristics of Epithermal Mineralization in Block Jalur 7 Bolaang Mongondow Regency, North Sulawesi - Firdaus F; Niciawati Dg Malureng; Hasbi Bakri; Muhamad Hardin Wakila; Anshariah Anshariah; Rizky Nurul Aulia (CV Insight Publisher, 2025)
Indonesia has the potential as an area containing large reserves of gold and sulfide minerals. One of the areas with the potential to produce gold is Bolaang Mongondow Regency, North Sulawesi Province. This study aims to identify the characteristics of epithermal deposition mineralization, including texture and the presence of mineralization, to determine its paragenesis. The analysis methods used are petrography, mineralogy, and X-ray Diffraction (XRD). As many as six samples in the test well are described megascopically and polarization microscopically, which have been ground into clay-sized fractions and analyzed using the X-ray Diffraction (XRD) method to detect clay minerals and other altered mineral associations. The quartz texture present at the research location based on megascopic observations is generally dominated by saccharoidal, vuggy, mold, banded, and chalcedonic textures. The identified minerals are generally dominated by base metal minerals, with paragenesis in sequence being pyrite, chalcopyrite, galena, hematite, ilmenite, and geothite. Alterations in the research area are in the form of Argillic, Silicic, Silica-Carbonate, and propylitic zones. The study's results concluded that the type of mineralization in Bolaang Mongondow Regency, North Sulawesi, is of the low-sulfidation epithermal type.